Modification of photosynthetic regulation in tomato overexpressing glutathione peroxidase - Herbette, Stephane; Menn, Aline Le; Rousselle, Patrick; Ameglio, Thierry; Faltin, Zehava; Branlard, Gérard; Eshdat, Yuval; Julien, Jean-Louis; Drevet, Joël R.; Roeckel-Drevet, Patricia (Biochimica et biophysica acta, 2005)
To investigate the function of glutathione peroxidase (GPX) in plants, we produced transgenic tomato plants overexpressing an eukaryotic selenium-independent GPX (GPX5). We show here that total GPX activity was increased by 50% in transgenic plants, when compared to control plants transformed with the binary vector without the insert (PZP111). A preliminary two-dimensional electrophoretic protein analysis of the GPX overexpressing plants showed notably a decrease in the accumulation of proteins identified as rubisco small subunit 1 and fructose-1,6-bisphosphate aldolase, two proteins involved in photosynthesis. These observations, together with the fact that in standard culture conditions, GPX-overexpressing plants were not phenotypically distinct from control plants prompted us to challenge the plants with a chilling treatment that is known to affect photosynthesis activity. We found that upon chilling treatment with low light level, photosynthesis was not affected in GPX-overexpressing plants while it was in control plants, as revealed by chlorophyll fluorescence parameters and fructose-1,6-biphosphatase activity. These results suggest that overexpression of a selenium-independent GPX in tomato plants modifies specifically gene expression and leads to modifications of photosynthetic regulation processes.